Rasch Analysis of Lebanese Nurses’ Responses to the EIS Questionnaire - Michael Clinton (SAGE Open, 2014)
This study examined the psychometric characteristics of a 32-item modified version of the Ethical Issues Scale (EIS). Data were collected from 59 registered nurses at the American University of Beirut Medical Centre (AUBMC). Data were analyzed using WINSTEPS Rasch analysis software. The four-category EIS rating scale needs modification for future studies in Lebanon. All EIS scale items need rewording prior to translation into Arabic to avoid confusion among Lebanese nurses. Principal component analysis (PCA) of residuals indicated the possible presence of additional dimensions. Additional EIS items are needed to improve targeting.